Social-Psychological Aspects of Communication of Physically Disabled Unemployed Persons - Hunbikova, Zuzana; Wertag, Anja; Vukelic, Anton (2007)
The studies of a work market clearly show that the unemployment is not only an economical event, which is a consequence of a lack of demand or coming recession in economy. Cultural and social stratification of society is responsible for the fact that some part of population is not well adapted to a changing structure of demand for jobs. Young, old and handicapped people are the groups of people most affected by the unemployment. Possibilities of a solution of handicapped unemployed position and detailed analysis were carried out on the basis of research of social-psychological aspects in relation to the handicapped unemployed. Finding of possible solutions is not so easy in practice. The research documents many negative effects of the unemployment on a man. These can result in high expenses from the side of society. In many cases the reduction of the stress connected with the unemployment and support of the activity of an individual in search foe a new job would be sufficient. Negative changes in the behaviour of the handicapped unemployed including loss of communicative skills may be observed with the prolongation of unemployment period. Negative attitude toward the society and a pessimistic attitude toward their own life are the other consequences.
Projekt MZOS
ENG